(untitled) (Studia Prawnicze / The Legal Studies, 1963)
The colossal progress made by science in recent times has given a number of new and highly important disciplines. Further specialization may lead to the disintegration of science. The place of scientists who in the past encompassed universal knowledge is today taken by higly specialized experts in very narrow fields. On the other hand, the close interrelation between all fields of life, nature and man obviously calls for a close interrelation of all sciences. Moreover there have emerged new branches of science which link problems of natural and social life. Integration of the separate disciplines of science and the intimate relation of research into all phenomena with all the accompanying circumstances are prequisites to the further development and progress of science as a whole. С. P. Snow wrote recently: ’’The habit of truth, on which science depends- as no other human activity does, is in itself a moral habit; investigation is in itself a moral act”. Proper evaluation is therefore decisive for the value of any research, any creative scientific work. This leads us to the wider conclusion: on which both theory and practice are at one, that is the principle of unity of all science. Errors committed in the past have frequently exposed law to the jibes of satirists and caricature artists, and provided material for masters of literature. Although it has been rather the practitioner of the legal profession which has constituted the main target, yet jurisprudence has not, and rightly so been spared. Socialism alone can overcome what Engels called ’’the legal view” — conservatism and dogmatism — and ensure rehabilitation by according to the science of law the appropriate rank and significance due to it Having once overcome the errors committed or not committed, jurisprudence should develope on a scale which its importance justifies. Today, jurisprudence is closer to social practice than over in the past. The marked trend towards specialization, however, with the consequent separation and subdivision of the various disciplines of law, has done no little harm. The major responsibility to be shouldered by jurists — scientific. workers — therefore, to liquidate these delaterious trends, to develop closer co-operation between the various disciplines of law and between jurisprudence and such other branches of the social sciences as philosophy, sociology, economics and history. The co-operation should embrace spheres of both theory and practice. The study, conducted by specialists in various disciplines, of the current development in socialist countries involves the study of various aspects of the same phenomena. The larger the number of disciplines encompassed and the wider the results taken into account, the more comprehensive the achievements of research. Thus, scientific progress calls not only for the synchronization and co-ordination of research as between the specific disciplines of the social sciences, but also necessitates taking into account the research conducted by technologists, naturalists and mathematicians. The Institute of Legal Sciences of the Polish Academy of Sciences has already taken steps towards the integration of certain research work. Our efforts are being directed towards the development -of co-operation: within the framework of the legal sciences — intersectoral; between theory and practice; between representatives of the sciences of law and of other domains of the social sciences. Particular importance is attached to research concerning issues related,to the administration of national economy, and to research into the conditions of peaceful coexistence as between the two social and economic systems. Poland considers these fields of research to be of utmost importance to national economy — a fact which explains why these issues take priority in the Institute’s research programme. Our plans are, however, not restricted to those two issues. Let us consider examples of other research projects now under way. These concern the development of socialist democracy (the problem of the organization and activity of People’s Councils, the participation of civic organizations in the performance of state tasks, and the problem of the functional mechanism of institutions of socialist democracy); the protection of social property, problems related to the transformation of the agricultural system, key problems of labour law, and problems bound up with the development and activity of the Council for Mutual Economic Aid. The Institute conducts its research work collectively. The various departments and research units are not composed of specialists in a single field. To give an example — specialists in civil, administrative and public law, as well as economists and sociologists are working in one unit on the problem of administration of national economy. Similarly, representatives of allied fields in the social sciences, such as philosophy, economics, sociology and history, co-operate in other research units. Other participants in the work of the units include practitioners such as judges and prosecutors, official of the Labour and Pay Committee, of the Institute of Agricultural Economics, journalists, employees of various branches of state administration, members of the People’s Councils, and civic leaders. The units function by preparing monographs which serve as basic synthesis, holding joint meetings and scientific discussions etc. The dominant principle at the Institute is that of collective work. In none of our work can we or should we restrict ourselves to the area of our individual countries. Although history and life pose problems which are not universally identical, yet we ought to benefit from one another’s achievements and experience. That we do in many sectors of life — in politics and economics — so that we cannot fail to do the same in science, and particularly in the field which concerns us, namely jurisprudence. Division of labour, co-operation and co-ordination in the economic sector — referred to by Prime Minister Krushchev in his work on current problems of the world socialist system — must be reflected in scientific research. The practical value of our science will increase as our research becomes more complex. This is the only way to the realization of the thesis that ’’science must become a direct productive force in the full sense of the word”. By broadening our scientific base, we shall be able more effectively to conduct cur scientific dialogue with the capitalist world. This ideological contest, obviously, is an essential factor in peaceful coexistence. Consequently, it is exceptionally important that we exchange experience and views on the co-operation between jurisprudence and other branches of social science and on international co-operation in the domain of jurisprudence. Such exchange will serve to enrich the programme of every Institute and will enable the Institutes to adopt recommendations and decisions of common application. Even if we advance only a single step, that will mean that the research and co-ordination set in motion will have been of fundamental importance.